Workers' Struggles, Past and Present: A "Radical America" Reader - Seixas, Peter (Labour / Le Travail, 1985)
This article reviews the book, "Worker's Struggles, Past and Present: A "Radical America" Reader," edited by James Green.
Keywords: Employees; GREEN; James; Nonfiction; REVIEWS; WORKER'S Struggles; Past & Present: A Radical America Reader (Book); books